2010
DOI: 10.1193/1.3478312
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Hazard Mapping of California considering Site Effects

Abstract: In this paper, we have combined the U.S. Geological Survey's National Seismic Hazard Maps model with the California geologic map showing 17 generalized geologic units that can be defined by their VS30. We regrouped these units into seven VS30 values and calculated a probabilistic seismic hazard map for the entire state for each VS30 value. By merging seismic hazard maps based on the seven different VS30 values, a suite of seismic hazard maps was computed for 0.2 and 1.0 s spectral ordinates at 2% probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Comparison of seismic hazard and building inventory parameters Site-specific V S30 incorporates V S30 values on 0.05-degree PSHA grid based on a simplified V S30 map of California(Kalkan et al 2010). Both ShakeMap correction(Wald et al 2005) and site-specific correction are based on National Earthquake Hazards Reduction Program (NEHRP) site classifications and amplification factors.…”
mentioning
confidence: 99%
“…Comparison of seismic hazard and building inventory parameters Site-specific V S30 incorporates V S30 values on 0.05-degree PSHA grid based on a simplified V S30 map of California(Kalkan et al 2010). Both ShakeMap correction(Wald et al 2005) and site-specific correction are based on National Earthquake Hazards Reduction Program (NEHRP) site classifications and amplification factors.…”
mentioning
confidence: 99%
“…First, Pullammanappallil et al (2006) and Louie et al (2010) showed that for 13 PBR sites V S30 is on average about 660 m/s. Both linear wave propagation theory (e.g., Aki and Richards 2002) and example calculations in Kalkan et al (2010) predict that decreased V S30 leads to slightly stronger ground motions than for the assumed conditions for the maps. For such rocks, the probability of consistency would decrease slightly when this is considered.…”
Section: To What Extent Are the New (2008) Hazard Maps Consistent Witmentioning
confidence: 96%
“…The objective of the national hazard model is to predict the hazard for a generic site with V S30 = 760 m/s, so the annual exceedance rate curves calculated for the national maps for the site of the PBR are not site-specific curves. Kalkan et al (2010) recalculated the seismic hazard for California considering site effects. Because PBRs typically form in granitic terranes, most will be in the V S30 = 760 m/s category used by Kalkan et al (2010), for which the hazard is identical to the national maps.…”
Section: To What Extent Are the New (2008) Hazard Maps Consistent Witmentioning
confidence: 99%
See 2 more Smart Citations